Neck Residue of Nasopharyngeal Carcinoma (NPC): Timing of Diagnosis and Treatment - Ferucha Moulanda; Marlinda Adham (INTERNATIONAL JOURNAL OF NASOPHARYNGEAL CARCINOMA, 2021)
Introduction: Prognosis of patients with NPC has improved but the risk of persistence regional of disease is still a critical problem. Timing of diagnosis the condition along with immediate yet appropriate treatment should be considered. Case report: Female 35 year-old diagnosed with NPC T2N3M0 and had finished neo-adjuvant chemotherapy (NAC) continued with chemoradiation (CRT) from July until December 2020. Clinical follow up on January 2021 showed palpable and fixated lymph node at level V of right neck sized 3x3x2.5 yet no mass identified at nasopharynx area. Patient was clinically diagnosed as neck residue of NPC and further management choices between early neck dissections or adjuvant chemotherapy (AdjCT) was still debatable in the multidisciplinary team discussion.  Conclusion: Neck residue diagnosis for high risk features of NPC should be made early. Immediate appropriate treatment should be considered since its associated with prognosis and overall survival of NPC patient